1989
DOI: 10.1128/mcb.9.11.5134
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances and mechanisms of inhibition of translation by secondary structure in eucaryotic mRNAs.

Abstract: This paper describes in vitro experiments with two types of intramolecular duplex structures that inhibit translation in cis by preventing the formation of an initiation complex or by causing the complex to be abortive. One stem-loop structure (AG = -30 kcal/mol) prevented mRNA from engaging 40S subunits when the hairpin occurred 12 nucleotides (nt) from the cap but had no deleterious effect when it was repositioned 52 nt from the cap. This result confirms prior in vivo evidence that the 40S subunit-factor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
467
5
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 595 publications
(507 citation statements)
references
References 40 publications
33
467
5
1
Order By: Relevance
“…Expression of the CAT-reporter gene, uORF F, and uORF F::HA under control of structural mutations introduced in the CaMV 35S RNA leader+ A: Resolution of in vitro-translated products in 16+5% SDS-PAGE using the Tricine discontinuous buffer system+ Constructs as depicted in Figure 2 and Table 1; translation efficiency and migration of CAT, as well as migration of uORF F (wt, pMH161, pMH162, pMH163, pMH172, pMH215) or uORF F::HA (wt9, pMH1619, pMH1629, pMH1639, pMH1729, pMH2159) are indicated+ B: Immunoprecipitation of the uORF::HA from pMH163, pMH1639, and pMH2159 translation in vitro+ (Fütterer et al+, 1996)+ Expression of reporter genes under the influence of the shunt-competent CaMV and RTBV pregenomic RNA leaders has been studied in a broad range of experimental conditions: in transiently transfected plant protoplasts (Fütterer et al+, 1993), in vitro (Schmidt-Puchta et al+, 1997), and in planta (Schärer-Hernández & Hohn, 1998)+ Ribosome shunt occurs in plant tissues and cell cultures derived from both CaMV host and nonhost plants, indicating that shunting does not depend on host-specific factors+ In this work, we demonstrate that ribosome shunt occurs on a synthetic mRNA leader just as well as on the viral leader+ Although it has been documented only for a few mRNAs, nonlinear ribosome migration seems to operate in diverse systems and therefore might be considered as a general alternative mechanism for the initiation of translation in eukaryotes+ Nonlinear ribosome migration remains a rather poorly described mechanism for translation initiation in eukaryotes+ Extensive studies on the CaMV pregenomic 35S RNA have shown that ribosome shunt depends exclusively on cis-acting elements in the leader: a lowenergy, elongated hairpin structure preceded by a short ORF terminating upstream (Dominguez et al+, 1998;Hemmings-Mieszczak et al+, 1998;Pooggin et al+, 1998)+ In some of the other cases where shunting has been reported, stable stems also seem to be involved (Füt-terer et al+, 1996;Li, 1996;Yueh & Schneider, 1996)+ Based on the common structural features of the known viral shunt-competent leaders, a synthetic mRNA leader was designed, where the viral structure is precisely replaced by a short, low-energy hairpin+ This particular stem (Fig+ 5A) has been previously used as a device to efficiently interfere with scanning: too stable to be unwound by the scanning complex, it does provoke the 40S subunit stalling on the 59 side of the hairpin (hp7; Kozak, 1989a)+ Incorporation of the artificial hairpin within the viral flanking sequences indeed fully blocks ribosome scanning, but promotes efficient shunting (Table 1; pMH192, pMH193, and pMH195)+…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of the CAT-reporter gene, uORF F, and uORF F::HA under control of structural mutations introduced in the CaMV 35S RNA leader+ A: Resolution of in vitro-translated products in 16+5% SDS-PAGE using the Tricine discontinuous buffer system+ Constructs as depicted in Figure 2 and Table 1; translation efficiency and migration of CAT, as well as migration of uORF F (wt, pMH161, pMH162, pMH163, pMH172, pMH215) or uORF F::HA (wt9, pMH1619, pMH1629, pMH1639, pMH1729, pMH2159) are indicated+ B: Immunoprecipitation of the uORF::HA from pMH163, pMH1639, and pMH2159 translation in vitro+ (Fütterer et al+, 1996)+ Expression of reporter genes under the influence of the shunt-competent CaMV and RTBV pregenomic RNA leaders has been studied in a broad range of experimental conditions: in transiently transfected plant protoplasts (Fütterer et al+, 1993), in vitro (Schmidt-Puchta et al+, 1997), and in planta (Schärer-Hernández & Hohn, 1998)+ Ribosome shunt occurs in plant tissues and cell cultures derived from both CaMV host and nonhost plants, indicating that shunting does not depend on host-specific factors+ In this work, we demonstrate that ribosome shunt occurs on a synthetic mRNA leader just as well as on the viral leader+ Although it has been documented only for a few mRNAs, nonlinear ribosome migration seems to operate in diverse systems and therefore might be considered as a general alternative mechanism for the initiation of translation in eukaryotes+ Nonlinear ribosome migration remains a rather poorly described mechanism for translation initiation in eukaryotes+ Extensive studies on the CaMV pregenomic 35S RNA have shown that ribosome shunt depends exclusively on cis-acting elements in the leader: a lowenergy, elongated hairpin structure preceded by a short ORF terminating upstream (Dominguez et al+, 1998;Hemmings-Mieszczak et al+, 1998;Pooggin et al+, 1998)+ In some of the other cases where shunting has been reported, stable stems also seem to be involved (Füt-terer et al+, 1996;Li, 1996;Yueh & Schneider, 1996)+ Based on the common structural features of the known viral shunt-competent leaders, a synthetic mRNA leader was designed, where the viral structure is precisely replaced by a short, low-energy hairpin+ This particular stem (Fig+ 5A) has been previously used as a device to efficiently interfere with scanning: too stable to be unwound by the scanning complex, it does provoke the 40S subunit stalling on the 59 side of the hairpin (hp7; Kozak, 1989a)+ Incorporation of the artificial hairpin within the viral flanking sequences indeed fully blocks ribosome scanning, but promotes efficient shunting (Table 1; pMH192, pMH193, and pMH195)+…”
Section: Discussionmentioning
confidence: 99%
“…In vitro translation products were analyzed in an electrophoretic system (Schägger & von Jagow, 1987) that allows separation of the 4+6-and 7+9-kDa peptides derived from uORF F and the truncated CAT reporter gene, respectively (Fig+ 4A)+ An additional weak band migrating at the position of the expected uORF F product was indeed detected in the case of mutants with decreased stability within stem section I (pMH161, (Fig+ 2A) to replace the natural elongated hairpin structure of the wild-type leader+ All secondary structures used were based on published data demonstrating that an artificial stable hairpin can efficiently block 40S subunit scanning, even if not in direct proximity to the 59-terminal cap structure in the leader (Kozak, 1989a)+ Thus, hp7-type structures flanked by the CaMV 35S RNA leader terminal sequences were tested in translation in vivo and in vitro (Fig+ 3B)+ In both systems, replacement of the CaMV elongated hairpin structure by a short, low-energy stem, in either orientation (pMH188: Ϫ45 kcal/mol; pMH189: Ϫ46 kcal/mol), supports efficient translation, showing that the stem per se, and not its sequence, is recognized by the translation machinery+ Stability of the hair-FIGURE 3. Expression of the CAT-reporter gene under control of mutations in the leader+ A: Mutations in the 59 end (pMH176, pMH174, pMH119), 39 end (pMH150, pMH155, pMH164, pMH165, pMH167 pMH169, pMH177, pMH187)+ B,C: Structural mutations in stem section I (pMH175, pMH160, pMH158, pMH72, pMH163) and an artificial hairpin replacement in the CaMV 35S RNA leader (pMH188, pMH189, pMH191, pMH212, pMH200, pMH190)+ Mutations as depicted in Figures 2 and 5; expression levels in vivo and in vitro are represented by grey and black bars, respectively; resolution of in vitro translated products in 12% SDS-PAGE is shown in the lower panels; c in C indicates control with no external RNA included+ pin in pMH188 seems to be sufficient to support ribosome shunting, as extending the structure does not enhance translation further (Fig+ 3B; pMH190; Ϫ50 kcal/ mol)+ To analyze the mechanism of translation initiation on pMH188, we then introduced additional mutations that were previously found to affect translation under the control of the CaMV 35S RNA leader+ Deletion of uORF A and deletion of the complete 59-proximal unstructured region (Table 1; pMH191 and pMH212, respectively) seriously diminished translation when tested in the context of the pMH188 construct; deletion of most of the 39-proximal unstructured region (pMH200) had only a marginal effect on CAT expression (equivalent to constructs pMH174, pMH119, and pMH187 in the CaMV 35S RNA leader context, respectively; see Figs+ 2 and 5 for sequence of mutants)+ In vitro, as with constructs expressed under the control of the CaMV 35S RNA leader (Hemmings-Mieszczak et al+, 1998), translation on the pMH188 transcript is optimal at 30 8C and a potassium acetate concentration of 100 mM (Fig+ 6A)+ Altogether, the way the artificial low-energy stem supports translation in pMH188 appears similar to the translation mechanism occurring on the CaMV 35S RNA leader+ Generally, expression levels in vivo on the CaMV 35S RNA leader constructs parallel translation data in vitro indicating that our results reflect differences in translation efficiencies (Fig+ 3A)+ Constructs including artificial hairpins were expressed at a similar level in vivo as those under the control of the CaMV 35S RNA leader (Fig+ 3B); in in vitro experiments, however, their expression was slightly higher+ Differences in ionicstrength conditions between the two translation systems might be responsible for this effect+ In any case, when compared between themselves, all constructs with synthetic stems in the leader are expr...…”
Section: -But Not 39-proximal Sequences In the Camv 35s Rna Leader mentioning
confidence: 99%
See 1 more Smart Citation
“…with respect to tissue specificity or developmental stages. The 5'UTR sequence is highly conserved in the rat and in the human MR-and GR-cDNA, suggesting a specific function of this region in the regulation of mRNA stability and translational efficiency (Kozak, 1989).…”
Section: Regulationmentioning
confidence: 99%
“…Once initiated translation is a very efficient process and even fairly stable structural elements in the coding region of the mRNA will not hinder the advancing ribosome until the stop codon is encountered (Kozak, 1989). Stop codon recognition is not simply a default process due to the lack of a corresponding amino-acyl tRNA.…”
mentioning
confidence: 99%